Mediating Impact of Information Sharing In the Relationship of Supply Chain Capabilities and Business Performance among the Firms of Thailand - Sudawan Somjai; Kittisak Jermsittiparsert (International Journal of Supply Chain Management, 2019)
Thailand is considered one of the largest exporters and producers of foods and agricultural products, and play an important role in the economic development of Thailand. However, food industry produces a high income for the country. Its supply chain system still has some problems among different parties. There are lot of factors which effect the performance of food industry’s chain. It is difficult to choose one success factor to be improved since improving one factor could lead to a positive or even a negative impact on another factor. The study purpose is to explore the relationship between supply chain capabilities and information sharing towards the business performance. The data was drawn from 220 food companies in Thailand and the measurement scale was validated using structural equation modelling (SEM). The findings show that supplies chain management capabilities have positive and significant association with business performance. Similarly, information sharing also have positive and significant association with business performance and also has mediating impact. Thus, proposed model could also provide causal-effect determinants affecting supply chain performance for enhance the supply chain strategies to meet supply chain goals and also to guide decision makers with the pertaining information for implement such strategies.